Melanomacrophage Centers As a Histological Indicator of Immune Function in Fish and Other Poikilotherms - Steinel, Natalie C.; Bolnick, Daniel I. (Frontiers in Immunology, 2017)
Melanomacrophage centers (MMCs) are aggregates of highly pigmented phagocytes found primarily in the head kidney and spleen, and occasionally the liver of many vertebrates. Preliminary histological analyses suggested that MMCs are structurally similar to the mammalian germinal center (GC), leading to the hypothesis that the MMC plays a role in the humoral adaptive immune response. For this reason, MMCs are frequently described in the literature as “primitive GCs” or the “evolutionary precursors” to the mammalian GC. However, we argue that this designation may be premature, having been pieced together from mainly descriptive studies in numerous distinct species. This review provides a comprehensive overview of the MMC literature, including a phylogenetic analysis of MMC distribution across vertebrate species. Here we discuss the current understanding of the MMC’s function in immunity, and lingering questions. We suggest additional experiments needed to confirm that MMCs serve a GC-like role in fish immunity. Lastly, we address the utility of the MMC as a broadly applicable histological indicator of the fish (as well as amphibian and reptilian) immune response in both laboratory and wild populations of both model and non-model vertebrates. We highlight the factors (sex, pollution exposure, stress, stocking density, etc…) that should be considered when using MMCs to study immunity in non-model vertebrates in wild populations.